PENINGKATAN PEMAHAMAN KONSEP FAKTORISASI PRIMA DAN APLIKASINYA MENGGUNAKAN MEDIA KREATIVITAS SISWA BAGI GURU SD NEGERI ENTROP JAYAPURA PROVINSI PAPUA - Westy B. Kawuwung; Bonefasius Yanwar Boy; Epiphani I.Y. Palit (JURNAL PENGABDIAN PAPUA, 2020)
The aim of this service activity is to increase the understanding of Entrop Elementary School teachers about one of the basic concepts of mathematics, namely prime factorization, its application in solving mathematical problems, as well as creative aids that can be used in teaching the concept to students. The method used is the explanation of mathematical concepts about factors, prime factors, and prime factorization of a number with examples of its application in solving mathematical problems. After that, examples of teaching aids which can be used to explain prime factorization to students are given. The result of this activity is an increase in the understanding of Entrop Public Elementary School teachers about the mathematical concepts of prime factorization, this can be seen by comparing their pre-test and post-test scores. Of the 23 teachers who participated in the activity, 80% experienced an increase in the understanding of the concept.Keywords: entrop, factors, prime factors, prime factorization, mathematic